Caregivers' perceptions of aggressive behaviour in nursing home residents living with dementia: A meta‐ethnography. (22nd August 2018) - Nybakken, Solvor; Strandås, Maria; Bondas, Terese
Abstract: Aim: To explore how formal caregivers perceive and interpret aggressive behaviour in nursing home residents living with dementia, by synthesizing knowledge from published qualitative studies. Background: Nursing home caregivers are exposed to aggressive behaviour from residents living with dementia. The way caregivers perceive aggressive behaviour may affect their feelings and actions related to situations and thus nursing care. Knowledge about caregivers' perceptions of aggressive behaviour has previously not been synthesized. Design: Noblit and Hare's interpretative meta‐ethnography. Data sources: A systematic literature search in CINAHL, PubMed and Scopus supplemented by manual search strategies, were completed. Nine studies from five countries, published between 2001 ‐ 2015, met the research objective and inclusion criteria and were included. Finding: Five themes describing formal caregivers' perceptions and interpretation of residents′ aggressive behaviour emerged: "A manifestation of the disease"; "a way to express themselves and their needs"; "a reaction to caregivers" attitude and approach"; "a reaction to a stressful and demanding environment"; and "an unavoidable situation that seems impossible to solve". Themes were synthesized into the metaphor: 'tailoring using unpredictable patterns' and visualized in a model. Conclusion: Caregivers perceive and interpret aggressive behaviour related to the resident's illness and person, the caregiver's attitude and approach, or a demanding environment. Further research and theoretical development is important, as shown by different perceptions and interpretations, as well as central definitions in research publications. The study informs evidence‐based practice and health‐policy by showing the importance of developing reflective relational nursing care, knowledge, and competence in nursing homes.